ESTUDIO COMPARATIVO DEL ENSAMBLAJE DE COLEÓPTEROS EN DIFERENTES ÁREAS DE LA CANTERA SORATAMA, LOCALIDAD DE USAQUÉN, BOGOTÁ - A. Álvarez-Duarte; J.I. Barrera-Cataño (Universitas Scientiarum)
This study compared the abundance and composition of coleoptera assemblage in Soratama sandstonequarry. This quarry presents areas with different levels of abandonment. 857 adult’s beetles belonging totwelve families were captured. The highest abundance and diversity were found in the adjacent forest.The lowest values were found in areas without vegetation cover. Assemblage composition among areaspresented significant differences, probably because of structural and microclimatic conditions providedby habitats to species of coleoptera.